Pendampingan Anak dalam Pembelajaran Daring di Masa Pandemi Covid-19 - Dinda Clarita Salsadillah; Joko Mulyono (CIC Lembaga Riset dan Konsultan Sosial, 2022)
Covid-19 is a disease outbreak that has had an impact on various fields, including the education sector. Breaking the chain of transmission of Covid-19 is a strong foundation for implementing online learning. The role of parents is increasingly important in accompanying children to learn online. The research method used is qualitative, a phenomenological approach with Max Weber's Verstehen theory used in this article. This research found that parents experience many problems in accompanying their children to online learning, including parents who are required to be able to be teachers at home who do not have an understanding of material knowledge, the busyness of parents, and the number of children. Methods of accompanying children's learning that are carried out by parents by helping to work on difficulties with children's schoolwork, explaining material that children do not understand, helping to operate mobile phones when online learning. There are some parents who still choose to accompany their children to online learning as much as possible and some other parents prefer to take their children to tutoring places. Covid-19 merupakan wabah penyakit yang membawa dampak di berbagai bidang, termasuk sektor pendidikan. Memutus mata rantai penyebaran Covid-19 menjadi landasan kuat implementasi pembelajaran daring dilakukan. Peran orang tua kian penting dalam mendampingi anak belajar daring. Metode penelitian yang digunakan adalah kualitatif, pendekatan fenomenologi dengan teori Verstehen Max Weber digunakan dalam artikel ini. Penelitian ini menemukan bahwa orang tua mengalami banyak permasalahan dalam mendampingi anak belajar daring termasuk orang tua dituntut harus bisa menjadi guru di rumah yang tidak memiliki pemahaman pengetahuan materi, kesibukan orang tua, dan jumlah anak. Metode pendampingan belajar anak yang dilakukan orang tua dengan membantu mengerjakan kesulitan tugas sekolah anak, menjelaskan materi yang tidak dipahami anak, membantu mengoperasikan handphone saat belajar daring. Terdapat sebagian orang tua tetap memilih mendampingi anak belajar daring semampunya dan sebagian orang tua lain lebih memilih untuk membawa anaknya ke tempat bimbingan belajar.